TPACK-BASED MENTORING PROGRAM: AN ALTERNATIVE TO IMPROVE THE ICT COMPETENCY OF MADRASAH IBTIDAIYAH TEACHERS - Syibli Maufur; Ahmad Arifuddin; Dadan Setiawan (LP2M IAIN Sultan Amai Gorontalo, 2024)
This study aims to analyze the effectiveness of a mentoring program based on Technological Pedagogical and Content Knowledge (TPACK) in improving the information and communication technology competency and the quality of digital learning media of Madrasah Ibtidaiyah teachers. This study used a one-group pretest-posttest design. The sample of this study was 30 Madrasah Ibtidaiyah teachers in Cirebon City. The instruments used were a TPACK competency questionnaire and a digital learning media assessment rubric. Data were analyzed using paired sample t-test and descriptive analysis. The results showed that before mentoring, teachers' technological competency was in the low category (TK = 2.37; TPACK = 2.51), while mastery of material and pedagogy was in the medium to high category. After mentoring, all aspects of TPACK competency experienced a significant increase (p < 0.001) with a very large effect size, especially in technological knowledge (d = 2.89) and overall TPACK (d = 2.76). TPACK competency increased from the low category to the high category (M = 3.93). The digital learning media developed by teachers achieved a good rating (M = 3.28), with the aspect of material accuracy receiving the highest score (M = 3.57). The types of media developed included interactive learning videos (30%), interactive multimedia presentations (27%), and digital educational games (23%). This study proves that TPACK-based mentoring is effective in strengthening teachers' abilities to integrate technology, pedagogy, and content in learning at MI.